Boardwalk empire. The complete fourth season [videorecording (DVD)] - Winter, Terence
Atlantic City, February 1924: Picking up 8 months after the events of Season 3, Nucky Thompson is laying low at the end of the Boardwalk after barely surviving an overthrow by gangster Gyp Rosetti. But the calm will be short-lived, as Nucky faces new challenges, including a clash with a violent Harlem power broker, a battle with his brother Eli over Eli's college-age son, and the irresistible lure of lucrative- and perilous- opportunities in Florida.